Konsep Jaring Laba-Laba sebagai Dasar Ilmu dalam Bimbingan dan Konseling Islam - Atikatul Adawiyah; Irsyadunnas Irsyadunnas (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2024)
The spider-web concept is utilized as a metaphor to understand the interconnectedness of various aspects of human life in Islamic Guidance and Counseling, encompassing spiritual, emotional, social, and psychological dimensions. This study aims to analyze the relevance of this concept as a foundational framework in Islamic-based counseling. Employing library research methods, the study reveals that the concept supports a holistic approach emphasizing the importance of life balance and integration of life aspects to achieve individual harmony and well-being. The spider-web concept is proposed as a relevant approach to address the complexities of modern life.